Making Decisions Under Stress: Implications for Individual and Team Training. 1998
DOI: 10.1037/10278-006
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking skills in tactical decision making: A model and a training strategy.

Abstract: In this chapter we describe a model of decision-making skills under time stress, a training strategy based on that model, and experimental tests of the training strategy. A prime example of the kind of decision making 155

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 15 publications
1
75
0
1
Order By: Relevance
“…There are accounts of uncertainty in finance (Rowe, 1994), management (Priem, Love, & Shaffer, 2002), medicine (Brashers et al, 2003), negotiation (Bottom, 1998), military tactics (Cohen, Freeman, & Thompson, 1998), and engineering (Wojtkiewicz, Eldred, Field, Urbina, & Red-Horse, 2001). Problem solvers across these settings draw on an array of domain-specific tools and methods to deal with uncertainty, such as rapid prototyping in engineering and design (Skelton & Thamhain, 2003) and statistical procedures such as Monte Carlo simulations and computational modeling in the sciences.…”
Section: Reasoning Judgmentmentioning
confidence: 99%
“…There are accounts of uncertainty in finance (Rowe, 1994), management (Priem, Love, & Shaffer, 2002), medicine (Brashers et al, 2003), negotiation (Bottom, 1998), military tactics (Cohen, Freeman, & Thompson, 1998), and engineering (Wojtkiewicz, Eldred, Field, Urbina, & Red-Horse, 2001). Problem solvers across these settings draw on an array of domain-specific tools and methods to deal with uncertainty, such as rapid prototyping in engineering and design (Skelton & Thamhain, 2003) and statistical procedures such as Monte Carlo simulations and computational modeling in the sciences.…”
Section: Reasoning Judgmentmentioning
confidence: 99%
“…For example, Calderwood, Klein, & Crandall (1988) found that the first responses considered by chess masters tended to be high quality. Cohen and his colleagues (Cohen, Freeman, & Thompson, 1998;Cohen, 2002) found that after NDM-based training, decision strategies more nearly resembled the strategies used by experts and decisions more nearly resembled the decisions of experts.…”
Section: Does Empirically Based Warrant Make Sense?mentioning
confidence: 98%
“…reviewing prior experiences to derive new insights and lessons from mistakes); building mental models; and obtaining coaching." Another, related approach is to train the metacognitive skills by means of which decision makers monitor their own thinking and take corrective steps when problems are found (Cohen, Freeman, & Wolf, 1996;Cohen, Freeman & Thompson, 1998;. Such skills may be more general across different domains than the specific cues, patterns, and strategies that compose specialized expertise (Means et al, 1993;Kuhn, Amsel, & O'Loughlin, 1988).…”
Section: Empirical Warrants For Naturalistic Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…This last type is also called "critical thinking training" (CTT) [Blickensderfer et al, 1998;Cohen et al, 1998;Fowlkes et al, 1998]. We can notice that the event-based approach to training (EBAT) uses naturalistic decision making [Fowlkes et al, 1998] and is thus directly in the scope of our research question.…”
Section: Training Researchmentioning
confidence: 99%